Hubungan Negara dan Masyarakat dalam Perspektif Maqasid Al-Shari?Ah Tahir Ibn ?Ashur - Muslihun, Muslihun; Na`imah, Farida Ulvi (Proceedings of Annual Conference for Muslim Scholars, 2019)
This study discusses the relationship between the state and society in the review of maqasid al-shari‘ah construction of T{ahir Ibn ‘Ashur. The method used in this study uses qualitative through content analysis by T{ahir Ibn ‘Ashur. The data finding obtained from the relationship between state and society in the perspective of maqasid al-shari‘ah are two inseparable entities. The relationship between the two is an interesting theme discussed in the study of the state system. T{ahir Ibn ‘Ashur offers a conception of the basic values of building a society and the structure of religious state. The religious state can be achieved if each individual community holds fast to the Islamic religion because the basis of this religion besides teaching theological values also instills an ethic of social interaction simultaneously. As for the state’s position in the of T{ahir Ibn ‘Ashur belongs to the social category governed by the Islamic community